PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TPS DI SMA NEGERI 12 BANDA ACEH - Emda, Amna (Lantanida Journal, 2014)
Students are studying subjects that are required to play an active role in learning activities. The way that can be done to enable such students through the implementation of cooperative learning model, one of which is TPS. TPS application of cooperative learning in the learning of chemistry can stimulate students to express opinions or ideas, mutual cooperation, respect the opinions of others, helping to solve problems and develop students' creativity. Active student involvement in learning will lead to learning motivation that will have an impact on the improvement of learning outcomes